2005
DOI: 10.1207/s15328015tlm1704_12
|View full text |Cite
|
Sign up to set email alerts
|

PERSPECTIVES: Exploratory Thoughts Concerning Educational Reform With Problem-Based Learning In China

Abstract: The author, a novice problem-based learning (PBL) advocate in China and a young faculty member of the School of Stomatology at Wuhan University, joined a PBL tutorial group as an observer during his two-month visit at McMaster University. He describes his observations and thoughts as they relate to the current reform of health sciences education in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…According to the study of Lempp & Seale, competitive rather than cooperative characteristics were more common among clinical medical students [1], which does not necessarily apply to our Japanese cases. The Japanese approach towards education, which stresses didactic lectures and rote memorization -- that is to say, "teacher centered, examination-driven and passive learning," symbolizing an educational philosophy that is much like that of many East Asian nations, which TEO & Song et al found [9,25], may also have an effect on Japanese medical students. In other words, the seemingly favorable results of Japanese medical students noted in our study might be a by-product of curricular differences.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of Lempp & Seale, competitive rather than cooperative characteristics were more common among clinical medical students [1], which does not necessarily apply to our Japanese cases. The Japanese approach towards education, which stresses didactic lectures and rote memorization -- that is to say, "teacher centered, examination-driven and passive learning," symbolizing an educational philosophy that is much like that of many East Asian nations, which TEO & Song et al found [9,25], may also have an effect on Japanese medical students. In other words, the seemingly favorable results of Japanese medical students noted in our study might be a by-product of curricular differences.…”
Section: Discussionmentioning
confidence: 99%
“…For those familiar with the Japanese approach towards education, which stresses didactic lectures, book‐learning and memorisation, this historical trend may not be surprising. This philosophy is much like those of other East Asian nations in that it is teacher‐centred and examination‐driven, and it encourages passive learning 5 …”
Section: Discussionmentioning
confidence: 99%
“…To understand postgraduate clinical education before the 2004 reforms, one must understand the structure of Japanese clinical−academic departments. If the format of medical school in Japan originally hailed from Germany 4 and the pedagogical principles utilised seem Chinese, 5 then the organisation and operation of these clinical departments derive from a traditional Japanese hierarchical model. Clinical departments, known as ikyoku , 6 are headed by a department chair who single‐handedly controls virtually every aspect of the department.…”
Section: Postgraduate Medical Educationmentioning
confidence: 99%
“…When students had formed a certain understanding of the given question, but lack of knowledge hampered them to find the solution to the question, they should explore their established learning points respectively [7]. In the process of teaching, students were the main body, but the guidance from teachers should be stressed as well, which demanded teachers to give definite goals, provide learning materials and learning resources and use the teaching method of combining group discussions and lectures to complete the curriculum objectives.…”
Section: Introductionmentioning
confidence: 99%